Synthesis of TiO2 Nanoparticle-Embedded SiO2 Microspheres for UV Protection Applications - Asghar, Ghulam; Dong, Xue; Chae, Sudong; Saqlain, Shahid; Oh, Seungbae; Choi, Kyung Hwan; Jeon, Jiho; Woo, Chaeheon; Kim, Tae Yeong; Ahn, Jungyoon; Oh, Hyung Suk; Park, Jae Hyuk; et al. (Crystal Growth and Design, 2023)
Exposure to ultraviolet (UV) radiation induces many serious health issues. Because of serious health concerns, there is an urgent need to develop UV filters with better efficacy and high safety. For this purpose, titanium dioxide (TiO2) nanoparticles are the most desirable materials due to their excellent UV protection abilities. The use of TiO2 as sunscreens has raised some concerns about potential risks due to the formation of TiO2-mediated free radicals. Herein, TiO2 nanoparticles have been successfully embedded in silica (SiO2) microspheres using the emulsion synthesis method. The as-synthesized TiO2 nanoparticles embedded in silica microspheres have shown excellent UV protection ability. TiO2 nanoparticles embedded in silica microspheres suppress the photocatalytic properties compared to bare TiO2 nanoparticles, and these results indicate that TiO2-embedded silica microspheres are promising UV protection materials for sunscreen.
Keywords: Emulsion synthesis; Health concerns; Health issues; High safety; Potential risks; Protection application; Silica microspheres; TiO2 nano-particles; Ultraviolet filters; Ultraviolet protection